2022
DOI: 10.3390/land11081345
|View full text |Cite
|
Sign up to set email alerts
|

Pasture Management to Reduce the Risk of Acer pseudoplatanus Poisoning While Preserving Ecological Sustainability

Abstract: In spring, grazing equids may suffer from a severe rhabdomyolysis syndrome named atypical myopathy. This environmental intoxication results from ingestion of toxins contained in Acer pseudoplatanus seedlings. The aim of this study was to investigate the effectiveness of herbicide spraying and mowing to reduce the toxic pressure of sycamore seedlings. In a first experiment, the efficacy of three herbicides to eradicate seedlings was compared to mowing. In a second experiment, the influence of the mowing timing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…40 Since the seedlings were not selected but always eaten along grasses and forbs, we observed their ingestion as a byproduct of grazing. Ghislain et al 41 reported that 78−86% of seedlings disappear naturally on a pasture within three to four weeks. Nevertheless, as there is not only a direct proof of consumption on the field level by various distinct field methods but also on the chemical level as metabolites of HGA and MCPrG are further detected in urine and milk samples, the decrease in seedlings in experimental plots likely goes back to ingestion by the cows.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…40 Since the seedlings were not selected but always eaten along grasses and forbs, we observed their ingestion as a byproduct of grazing. Ghislain et al 41 reported that 78−86% of seedlings disappear naturally on a pasture within three to four weeks. Nevertheless, as there is not only a direct proof of consumption on the field level by various distinct field methods but also on the chemical level as metabolites of HGA and MCPrG are further detected in urine and milk samples, the decrease in seedlings in experimental plots likely goes back to ingestion by the cows.…”
Section: ■ Results and Discussionmentioning
confidence: 99%